Nature's Combinatorial Biosynthesis Produces Vatiamides A–F. Issue 27 (28th May 2019) - Moss, Nathan A.; Seiler, Grant; Leão, Tiago F.; Castro‐Falcón, Gabriel; Gerwick, Lena; Hughes, Chambers C.; Gerwick, William H.
Abstract: Hybrid type I PKS/NRPS biosynthetic pathways typically proceed in a collinear manner wherein one molecular building block is enzymatically incorporated in a sequence that corresponds to gene arrangement. In this work, genome mining combined with the use of a fluorogenic azide‐based click probe led to the discovery and characterization of vatiamides A–F, three structurally diverse alkynylated lipopeptides, and their brominated analogues, from the cyanobacterium Moorea producens ASI16Jul14‐2. These derive from a unique combinatorial non‐collinear PKS/NRPS system encoded by a 90 kb gene cluster in which an upstream PKS cassette interacts with three separate cognate NRPS partners. This is facilitated by a series of promiscuous intermodule PKS‐NRPS docking motifs possessing identical amino acid sequences. This interaction confers a new type of combinatorial capacity for creating molecular diversity in microbial systems. Abstract : Combination dock : A unique natural example of polyketide synthase/non‐ribosomal peptide synthetase combinatorial biosynthesis is reported. The vatiamides from the cyanobacterium Moorea producens are produced by a PKS/NRPS system encoded by a 90 kb gene cluster, from which the encoded enzymes interact via promiscuous docking domains with identical sequence to produce three distinct natural product series.